The Engagement Between MDSCs and Metastases: Partners in Crime - Trovato, Rosalinda; Canè, Stefania; Petrova, Varvara; Sartoris, Silvia; Ugel, Stefano; De Sanctis, Francesco (Frontiers in Oncology, 2020)
Tumor metastases represent the major cause of cancer-related mortality, confirming the urgent need to identify key molecular pathways and cell-associated networks during the early phases of the metastatic process to develop new strategies to either prevent or control distal cancer spread. Several data revealed the ability of cancer cells to establish a favorable microenvironment, before their arrival in distant organs, by manipulating the cell composition and function of the new host tissue where cancer cells can survive and outgrow. This predetermined environment is termed “pre-metastatic niche” (pMN). pMN development requires that tumor-derived soluble factors, like cytokines, growth-factors and extracellular vesicles, genetically and epigenetically re-program not only resident cells (i.e. fibroblasts) but also non-resident cells such as bone marrow-derived cells. Indeed, by promoting an “emergency” myelopoiesis, cancer cells switch the steady state production of blood cells towards the generation of pro-tumor circulating myeloid cells defined as myeloid-derived suppressor cells (MDSCs) able to sustain tumor growth and dissemination. MDSCs are a heterogeneous subset of myeloid cells with immunosuppressive properties that sustain metastatic process. In this review, we discuss current understandings of how MDSCs shape and promote metastatic dissemination acting in each fundamental steps of cancer progression from primary tumor to metastatic disease.